Physical-chemical characterization and biological assessment of simple and lithium-doped biological-derived hydroxyapatite thin films for a new generation of metallic implants - OKTAR, FAİK NÜZHET (ELSEVIER, 2018)
We report on the synthesis by PLD of simple and lithium-doped biological-origin hydroxyapatite (HA) films. The role of doping reagents (Li2CO3, Li3PO4) on the morphology, structure, chemical composition, bonding strength and cytocompatibility of the films was investigated. SEM investigations of the films evidenced a surface morphology consisting of particles with mean diameters of (5-7) mu m. GIXRD analyses demonstrated that the synthesized structures consisted of HA phase only, with different degrees of crystallinity, mainly influenced by the doping reagent type. After only three days of immersion in simulated body fluid, FTIR spectra showed a remarkable growth of a biomimetic apatitic film, indicative of a high biomineralization capacity of the coatings. EDS analyses revealed a quasi-stoichiometric target-to-substrate transfer, the values inferred for the Ca/P ratio corresponding to a biological apatite. All synthesized structures displayed a hydrophilic behavior, suitable for attachment of osteoblast cells. In vitro cell viability tests showed that the presence of Li2CO3 and Li3PO4 as doping reagents promoted the hMSC growth on film surfaces. Taking into consideration these enhanced characteristics, corroborated with a low fabrication cost generated by sustainable resources, one should consider the lithium-doped biological-derived materials as promising prospective solutions for a next generation of coated implants with rapid osteointegration. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Biological-derived hydroxyapatite; Lithium doping; Pulsed Laser Deposition; Sustainable resources; In vitro assessment; PULSED-LASER DEPOSITION; MESENCHYMAL STEM-CELLS; CARBONATED HYDROXYAPATITE; SYNTHETIC HYDROXYAPATITE; BIOMEDICAL APPLICATIONS; PHOSPHATE CERAMICS; BONE REGENERATION; SURFACE-ENERGY; COATINGS; TITANIUM